O território e as estratégias de permanência camponesa da comunidade Pedra Lisa no processo de expansão das lavouras de cana-de-açúcar em Quirinópolis/GO - Souza, Edevaldo Aparecido (2013)
This work analyzes the peasant community Pedra Lisa that constitutes one of the 21 sub-regions of the Quirinópolis‟ borough, predominantly the small farms and the activity with dairy cattle. There are families that are in the Pedra Lisa for over forty years, having built their lives and social relationships in this place. In this peasant existence there are conjugations social practices of other times, with incorporation of most modern technologies, in the perspective of an economy of the work and reduction of the human effort, in the household chores, as well as the facilities in the intercommunication and information on a larger scale. For this reason, the research, in the community Pedra Lisa, established its methodological paths composed of a theoretical referential on the themes discussed in the thesis and the empirical work, for knowledge of the reality experienced in the quotidian of the subjects surveyed. The investigation in field, conducted in different stages, through interviews, with annotations in field diary, established by insertion in the community, seeking to experience part of the socio-cultural practices in the place Pedra Lisa and record facts and landscapes from the photography. The objective of this research was to list the peasants values that still exist in the place Pedra Lisa, witnessing a historical memory, preserving identities of the past, made up of people and things, tangible and intangible elements. Thus, its territories also remain present, in a process of coexisting with the modern territories. This way, if their social practices still remain is because they are strong for the social groups that constitute them, leveraging its (re) existence. The research results were distributed into six chapters: the first and the second chapters portray, in descriptive and analytical form, the physical and cultural landscapes and the interrelationships with the lifestyles of the Cerrado‟s peasant and the agribusiness, indicating the possibility of the space isn‟t a being handled only by that hold financial resources, since the landscape revealed, from the place, allows the identification of forms and peasants territorial ties; the third chapter, is a reflection about the different social logics, identified in the place, especially, the peasantry and the of the agribusiness, analyzing the different social logics between the coexistences and its contradictions; the fourth chapter provides a discussion around the concepts of territory and territorial bonds that the peasants keep with the place, emphasizing their social practices with the dimension of the territorial ties and the means of the peasants of the Pedra Lisa if relate to their diverse institutions; the fifth chapter, discusses the relationship between the ways of peasant life and the modernity, in order to study the identification of the subjects involved, space/temporally, in the process of reoccupation of the Cerrado, trying to understand the social condition of the milk producers of the Pedra Lisa, face the transformations of the economic modernity and policies imposed on this place; and the sixth chapter, extend the place lived of the peasant of the Pedra Lisa community that continues to exist in a changing space.